THE ESTIMATION OF TAX-BENEFIT AUTOMATIC STABILIZERS IN SERBIA: A COMBINED MICRO-MACRO APPROACH - Ranđelović, Saša (Economic Annals, 2013)
The large volatility of GDP due to the economic crisis, particularly in transition economies, has brought the issue of automatic stabilizers back into the focus of economic policy. The vast majority of empirical literature in this field relates to the estimation of the size of automatic stabilizers in developed countries, usually based on macroeconomic data. On the other hand empirical literature on this topic based on micro data, particularly for transition economies, is limited. This paper provides an evaluation of the size of automatic stabilizers in one transition economy (Serbia), by combining tax-benefit simulation modelling based on micro data and econometric methods based on macroeconomic data. The results show that, in the case of shock, around 17% of fall in market income would be absorbed by automatic stabilizers. Although the stabilizing effects of the tax-benefit system in Serbia are lower than in other European countries, the total size of automatic stabilizers is close to the average value in these countries, due to the higher elasticity of demand to income. The results also show that progressivity-enhancing income tax reform would only slightly increase automatic stabilizers, due to the large informal economy and the large share of agriculture in total households’ income.